In vitro and in vivo evaluation of chlorhexidine salts as potential alternatives to potassium dichromate for Eimeria maxima M6 oocyst preservation - Laverty, Lauren; Beer, Lesleigh C.; Martin, Kristen; Hernandez-Velasco, Xochitl; Juarez-Estrada, Marco A.; Arango-Cardona, Marcela; Forga, Aaron J.; Coles, Makenly E.; Vuong, Christine N.; Latorre, Juan D.; Señas-Cuesta, Roberto; Loeza, Ileana; et al. (Frontiers in Veterinary Science, 2023)
Coccidiosis caused by the Eimeria spp., an Apicomplexan protozoon, is a major intestinal disease that affects the poultry industry. Although most cases of coccidiosis are subclinical, Eimeria infections impair bird health and decrease overall performance, which can result in compromised welfare and major economic losses. Viable sporulated Eimeria oocysts are required for challenge studies and live coccidiosis vaccines. Potassium dichromate (PDC) is typically used as a preservative for these stocks during storage. Although effective and inexpensive, PDC is also toxic and carcinogenic. Chlorhexidine (CHX) salts may be a possible alternative, as this is a widely used disinfectant with less toxicity and no known carcinogenic associations. In vitro testing of CHX gluconate and CHX digluconate exhibited comparable oocyst integrity and viability maintenance with equivalent bacteriostatic and bactericidal activity to PDC. Subsequent use of CHX gluconate or digluconate-preserved Eimeria oocysts, cold-stored at 4°C for 5 months, as the inoculum also resulted in similar oocyst shedding and recovery rates when compared to PDC-preserved oocysts. These data show that using 0.20% CHX gluconate could be a suitable replacement for PDC. Additionally, autofluorescence was used as a method to evaluate oocyst viability. Administration of artificially aged oocysts exhibiting >99% autofluorescence from each preserved treatment resulted in no oocyst output for CHX salt groups.